2015
DOI: 10.3892/ijmm.2015.2157
|View full text |Cite
|
Sign up to set email alerts
|

Maternal peripheral blood natural killer cells incorporate placenta-associated microRNAs during pregnancy

Abstract: Although recent studies have demonstrated that microRNAs (miRNAs or miRs) regulate fundamental natural killer (NK) cellular processes, including cytotoxicity and cytokine production, little is known about the miRNA-gene regulatory relationships in maternal peripheral blood NK (pNK) cells during pregnancy. In the present study, to determine the roles of miRNAs within gene regulatory networks of maternal pNK cells, we performed comprehensive miRNA and gene expression profiling of maternal pNK cells using a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Of note, C19MC-mediated paracrine effects are very likely virus-specific, because they do not protect, and even potentiate, CMV infection (Delorme-Axford et al, 2013). Other studies also demonstrated an involvement of exosomal C19MC miRNAs in cell-to-cell communication, notably between placenta and immune cells (Kambe et al, 2014; Ishida et al, 2015). In vitro , miR-517a-3 secreted from human choriocarcinoma (BeWo) cells can be transferred into the immortalized T lymphocyte (Jurkat) cells, where it downregulates the expression of endogenous PRKG1 mRNA.…”
Section: The Primate-specific Paternally-expressed C19mc Mirna Genesmentioning
confidence: 90%
See 1 more Smart Citation
“…Of note, C19MC-mediated paracrine effects are very likely virus-specific, because they do not protect, and even potentiate, CMV infection (Delorme-Axford et al, 2013). Other studies also demonstrated an involvement of exosomal C19MC miRNAs in cell-to-cell communication, notably between placenta and immune cells (Kambe et al, 2014; Ishida et al, 2015). In vitro , miR-517a-3 secreted from human choriocarcinoma (BeWo) cells can be transferred into the immortalized T lymphocyte (Jurkat) cells, where it downregulates the expression of endogenous PRKG1 mRNA.…”
Section: The Primate-specific Paternally-expressed C19mc Mirna Genesmentioning
confidence: 90%
“…Their levels rapidly decline after delivery, further arguing that exosome-mediated delivery of C19MC in immune cells occurs during pregnancy. Yet, their putative roles in immunity pathways remain to be unveiled (Ishida et al, 2015). Altogether, these data lend experimental support to the concept that C19MC miRNA-containing exosomes mount cellular responses to protect fetus from maternal immune activation and viral infection (Bullerdiek and Flor, 2012; Mouillet et al, 2014; Tong et al, 2018).…”
Section: The Primate-specific Paternally-expressed C19mc Mirna Genesmentioning
confidence: 99%
“…C19MC is nearly exclusively expressed in the placenta (Bentwich et al 2005;Luo et al 2009), suggesting an important role in placental development and function. Specific function and regulation of C19MC in the placenta is not completely clear yet (reviewed by (Mouillet et al 2015)), but three functional complexes are likely to be influenced by C19MC: these are viral resistance (Delorme-Axford et al 2013), AR: induced abortion; MSA: spontaneous abortion; TE: delivery at term + − 2 weeks; SD: standard deviation; nfold max/min: ratio of highest expression divided by lowest expression implantation and placenta development (Anton et al 2015;Ding et al 2015;Xie et al 2014), and immunomodulation in terms of fetal-maternal cross talk (Bullerdiek and Flor 2012;Ishida et al 2015;Kambe et al 2014). This is, to our knowledge, the first report investigating the expression of C19MC miRNAs and miR-371-3 cluster in the placental tissue comparing three groups (induced and spontaneous abortions and full-term placentas) in a large cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that placental trophoblast cells are highly resistant to several virus infections and additionally confer their resistance to other nonplacental cells via exosomes containing, among others, specific miRNAs of C19MC. Furthermore, immunomodulatory functions related to the establishment and maintenance of embryo-maternal tolerance have also been assumed to be influenced by these miRNAs (Bullerdiek and Flor 2012;Ishida et al 2015;Kambe et al 2014). In addition, there is an increasing evidence that contribution to proper implantation and placenta development is another group of functions addressed by the miRNAs of both clusters (Xie et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this and other previous studies, the reference values of pregnancy‐associated placental miRNAs on C19MC (miR515‐3p, miR‐517a, miR‐517c and miR‐518b) increased as pregnancy progressed and rapidly decreased 1 day after delivery. Additionally, one study showed that the expression of C19MC miRNAs in pNK cells were significantly upregulated in the third trimester compared with the first‐trimester, and the rapid clearance of C19MC miRNAs from the pNK cells occurred after delivery . This suggests that C19MC miRNA regulates migratory and invasive behaviors of extravillous trophoblasts and plays a role in the establishment of the maternal–fetal interface .…”
Section: Discussionmentioning
confidence: 99%